When do the symptoms of autonomic nervous system malfunction appear in patients with Parkinson’s disease? - De Luka, Silvio R.; Svetel, Marina; Pekmezović, Tatjana; Milovanovic, Branislav; Kostic, Vladimir S. (Vojnosanitetski pregled, 2014)
Background/Aim. Dysautonomia appears in almost all patients with Parkinson’s disease (PD) in a certain stage of their condition. The aim of our study was to detect the development and type of autonomic disorders, find out the factors affecting their manifestation by analyzing the potential association with demographic variables related to clinical presentation, as well as the symptoms of the disease in a PD patient cohort. Methods. The patients with PD treated at the Clinic of Neurology in Belgrade during a 2-year period, divided into 3 groups were studied: 25 de novo patients, 25 patients already treated and had no long-term levodopa therapy-related complications and 22 patients treated with levodopa who manifested levodopa-induced motor complications. Simultaneously, 35 healthy control subjects, matched by age and sex, were also analyzed. Results. Autonomic nervous system malfunction was defined by Ewing diagnostic criteria. The tests, indicators of sympathetic and parasympathetic nervous systems, were significantly different in the PD patients as compared with the controls, suggesting the failure of both systems. However, it was shown, in the selected groups of patients, that the malfunction of both systems was present in two treated groups of PD patients, while de novo group manifested only sympathetic dysfunction. For this reason, the complete autonomic neuropathy was diagnosed only in the treated PD patients, while de novo patients were defined as those with the isolated sympathetic dysfunction. The patients with the complete autonomic neuropathy differed from the subjects without such neuropathy in higher cumulative and motor unified Parkinson’s disease rating score (UPDRS) (p < 0.01), activities of daily living scores (p < 0.05), Schwab-England scale (p < 0.001) and Hoehn-Yahr scale. There was no difference between the patients in other clinical-demographic characteristics (sex, age at the time of diagnosis, actual age, duration of disease, involved side of the body, pain and freezing), but mini mental status (MMS) score and Hamilton depression and anxiety rating scale were significantly lower (p < 0.05). Conclusion. Our results confirm a high prevalence of autonomic nervous system disturbances among PD patients from the near onset of disease, with a predominant sympathetic nervous system involvement. The patients who developed complete autonomic neuropathy (both sympathetic and parasympathetic) were individuals with considerable level of functional failure, more severe clinical presentation and the existing anxiety and depression.
Keywords: parkinson disease; autonomic nervous system